Comparative study on the quality and food safety - Paula-Angela Vidraşcu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
The issues addressed in this paper makes a significant contribution to solving the complexity irregularities occurred in the development of environmental achievements. Quality and food safety is now a consumer law that directly reflects the quality of life. So this topic gives a particular importance to the work of the bodies created to defend the interests of all consumers. This study has an important role both in the short and long term through proper understanding of the terms of quality and food safety and implementation of strict hygienic-sanitary rules. The essential aim of this article is the integration of environmental awareness, which can stop the degradation and disappearance of the planet. Thus through the implementation of the adoption and application of strict orders regarding compliance with hygienic-sanitary rules can result in increased development and maintenance of environmental performance in a competitive economy . Quality is and will always be a very important competitive factor.
Keywords: 330; Food quality; food safety; ecological success; eating behavior; sustainable development